2005
DOI: 10.1161/01.res.0000162100.52009.38
|View full text |Cite
|
Sign up to set email alerts
|

SDF-1α/CXCR4 Axis Is Instrumental in Neointimal Hyperplasia and Recruitment of Smooth Muscle Progenitor Cells

Abstract: Abstract-Recent evidence infers a contribution of smooth muscle cell (SMC) progenitors and stromal cell-derived factor (SDF)-1␣ to neointima formation after arterial injury. Inhibition of plaque area and SMC content in apolipoprotein E-deficient mice repopulated with LacZ ϩ or CXCR4 Ϫ/Ϫ BM or lentiviral transfer of an antagonist reveals a crucial involvement of local SDF-1␣ and its receptor CXCR4 in neointimal hyperplasia via recruitment of BM-derived SMC progenitors. After arterial injury, SDF-1␣ expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
333
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 340 publications
(361 citation statements)
references
References 49 publications
25
333
2
1
Order By: Relevance
“…1). It is known that platelets express and secrete the CXC chemokine SDF-1␣ (CXCL12), which has recently been implicated in attracting circulating cells to the vascular wall (27,42,43). Expression of the cognate receptor for SDF-1␣, CX-chemokine receptor 4 (CXCR4) has been shown to crucially support organ-selective hematogenous metastasis of melanoma cells to the lung (32).…”
Section: Resultsmentioning
confidence: 99%
“…1). It is known that platelets express and secrete the CXC chemokine SDF-1␣ (CXCL12), which has recently been implicated in attracting circulating cells to the vascular wall (27,42,43). Expression of the cognate receptor for SDF-1␣, CX-chemokine receptor 4 (CXCR4) has been shown to crucially support organ-selective hematogenous metastasis of melanoma cells to the lung (32).…”
Section: Resultsmentioning
confidence: 99%
“…If the progenitor cells had invaded and proliferated, the media structure should have been disarranged. Moreover, on the third day after denudation, the progenitor cells had not fully been recruited in the media (53,54). Thus, the PCNApositive cells were thought to be pre-existing medial SMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, SDF-1 contributes to the stabilization of neo-vessel formation by recruiting CXCR4 + PDGFR + ckit + smooth muscle progenitor cells during recovery from vascular injury [64]. Although Aghi et al suggested that SDF-1 did not recruit pericytes in glioma models [58], it is likely that specific tumor types could require recruitment of BM-derived CXCR4 + pericyte progenitors in a SDF-1-dependent manner [65].…”
Section: Multiples Roles Of Sdf-1 In Governing Neo-angiogenesis In Vivomentioning
confidence: 99%